Genome wide profiling of tongue and cheek cancer using high resolution array based CGH - Vincent-Chong, V.K.; Rahman, Z.A.A.; Zakaria, Z.; Tay, K.K.; Ismail, S.M.; Zain, R.B. (Elsevier, 2011)
Introduction: Tongue and cheek cancer have different behaviors. In order to understand these behaviors, there is a need to look into the chromosomal alterations and gene pathways that maybe associated with oral cancer at these sites. Therefore, the objective of this study is to determine the differences in chromosomal aberrations and gene pathways involved in tongue and cheek cancer using high resolution array CGH.